Variation in trauma-related behavioral effects using a preclinical rat model of three predator exposure stress. (2nd January 2022) - Scott, Emily; May, Matthew; Silva, Gabriella; Taylor, Rachel; Fenlon, Nicole; Lowery-Gionta, Emily; Matson, Liana
Abstract: The underlying mechanisms of trauma-related disorders are challenging to discover and the disorders are difficult to treat, in part due to the complex and varied expressions of response to traumatic stress. These challenges will be easier to overcome as more is understood about the variability in response to trauma. Incorporating assessment of variability into animal models of traumatic stress may allow better translation to clinical research and treatment development. In this study, we characterized variability in behavioral responses following traumatic stress exposure using a predator exposure (PE) animal model. Elevated plus maze (EPM) and acoustic startle response (SR) were used to study avoidance and arousal symptoms in male Sprague–Dawley rats. Behavioral data were compared between control ( n  = 31) and predator-exposed ( n  = 30) rats. PE behavior was clustered using k-means principal components analysis. Four clusters and three distinct subgroups were identified and were characterized as avoidant (Cluster 4, 30%), moderately avoidant (Clusters 2 and 3, 49%), and unaffected (Cluster 1, 17%). These results demonstrate that rodent responses to PE are varied, similar to human presentations following traumatic stress, suggesting it may be possible to develop treatment strategies for varied symptom presentations using a preclinical animal model.